The Influence of Competency and Organizational Culture Through Motivation on Employee Performance at the Office of the Port Master and Port Authority of Class Iv Muara Sabak - Bella Beliana Bintang; M. Zahari; Osrita Hapsara (Greenation Research & Yayasan Global Resarch National, 2025)
Employee performance is a crucial factor in supporting the success of public sector organizations, particularly in providing effective and quality services. Employee performance is influenced by various internal organizational factors, including competence, organizational culture, and work motivation. This study aims to analyze the influence of competence and organizational culture on employee performance through work motivation at the Muara Sabak Class IV Harbormaster and Port Authority Office (KSOP). This study used a quantitative approach with a survey method. The population in this study was all 63 employees of the Muara Sabak Class IV KSOP Office, and the entire population served as the research sample (saturated sample). Data collection was conducted through a Likert-scale questionnaire. Data analysis used path analysis with the Partial Least Squares (PLS) approach to test the direct and indirect effects between variables. The results showed that competence and organizational culture had a positive and significant effect on work motivation. Furthermore, work motivation had a positive and significant effect on employee performance. Furthermore, competence and organizational culture also indirectly influenced employee performance through work motivation. The results of this study indicate that improving employee competency and strengthening a positive organizational culture can increase work motivation, which ultimately impacts employee performance.